DETERMINATION OF WATER QUALITY STATUS OF SITU CISANTI USING THE STORET METHOD - Gunawan, Ronald Krisna Rizki; Herawati, Heti; Sahidin, Asep; Zahidah, Zahidah (Jurnal Perikanan Unram, 2025)
Situ Cisanti has the main function which is, being utilized by the surrounding community for various activities such as plantations, fisheries and tourism activities. The many activities in Situ Cisanti have an impact on the decline in water quality in the waters of Situ Cisanti. The water quality in Situ Cisanti must meet water quality standards because Situ Cisanti is the zero point of the Citarum River so that it has a direct impact on fish farming activities and drinking water sources along the Citarum River. Determination of water quality status in a body of water can be done by several methods, one of which is the STORET Method. Through the STORET Method, the water quality status of Situ Cisanti can be determined. The method used is the survey method. Determination of sampling points is determined based on considerations of the zoning of the water body consisting of inlets, the middle of the waters and outlets. Data analysis is carried out by comparing it with water quality standards and scoring it. Based on the results, the water quality status of Situ Cisanti is categorized as "lightly to moderately polluted" with a score between -10 to -11 for class 1 water quality standards and is categorized as lightly polluted with a score of -10 for class 2 quality standards. So it can be concluded that it does not meet the quality standards set by Government Regulation Number 22 of 2021 for raw water for drinking water and fisheries activities.